Effect of tax rates, penalty rate, detection probability, cost of compliance, royalty rates, environmental regulations, and petroleum profit tax compliance the moderating role of trust in government: A conceptual framework - Ya’u, Abba; Saad, Natrah; Mas’ud, Abdulsalam (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2019)
The paper presents a theoretical framework on the moderating effect of trust in authority on the relationship between tax rates, penalty, detection probability, cost of compliance, royalty rates, environmental regulations, and petroleum profit tax compliance. The objective of the proposed framework is to expand the Allingham and Sandmo (1972) model of tax compliance by adding two more predictor variables relevant to the oil and gas industry (royalty rates and environmental regulations), and moderating variable (trust) to better explain the relationship. Allingham and Sandmo (1972) model received a lot of criticisms for not considering other non-human factors that can help in determining taxpayers’ compliance behavior, hence the expansion of the model to include new variables, purely non-human factors which are relevant to the industry in question. A thorough search of the following databases: Scopus database, Web of Science, Emerald, Google Scholar, among others was conducted to come up with the relevant and related literature on the subject matter. Providing empirical evidence through validation of this framework would have important implications for policymakers in host oil and gas producing countries, oil and gas operators, the deterrence theory as well as future research.